Arrays of 3D double-network hydrogels for the high-throughput discovery of materials with enhanced physical and biological properties. (1st April 2016) - Duffy, Cairnan; Venturato, Andrea; Callanan, Anthony; Lilienkampf, Annamaria; Bradley, Mark
Graphical abstract: Abstract: Synthetic hydrogels are attractive biomaterials due to their similarity to natural tissues and their chemical tunability, which can impart abilities to respond to environmental cues, e.g. temperature, pH and light. The mechanical properties of hydrogels can be enhanced by the generation of a double-network. Here, we report the development of an array platform that allows the macroscopic synthesis of up to 80 single- and double-network hydrogels on a single microscope slide. This new platform allows for the screening of hydrogels as 3D features in a high-throughput format with the added dimension of significant control over the compressive and tensile properties of the materials, thus widening their potential application. The platform is adaptable to allow different hydrogels to be generated, with the potential ability to tune and alter the first and second network, and represents an exciting tool in material and biomaterial discovery.